Overdose intake of Neu5Gc triggers colorectal inflammation and alters liver metabolism - Teng Yuan; Peidong Yang; Anjing Zhang; Jing Li; Ziyin Han; Shuqi Yang; Yihamu Jimu; Fanli Kong; Dengke Pan; Keren Long; Mingzhou Li; Lu Lu (Food and Agricultural Immunology, 2023)
ABSTRACTA positive correlation between massive red meat consumption with colorectal cancer had been reported. Given the complexity of meat components, we focused on investigating the role of Neu5Gc in human healthy. Two groups, either feeding with normal and overdose concentration of Neu5Gc for two weeks, to mimic the normal and overconsumption of red meat conditions in human, respectively. The colorectal transcriptomes revealed that Neu5Gc promotes intestinal immune response and identified the hub genes positively correlated with colorectal cancer such as Tnf, Cd19, Muc13, and Nso2,. The colorectal cancer patients have a 25–30% chance of developing liver metastases, thus we sequenced the liver and revealed the role of Neu5Gc in regulating cell metabolism. Moreover, we found that Neu5Gc negatively regulates the expression of Cmah. We conclude that high Neu5Gc intake promotes colorectal inflammatory responses in ApcMin/+ mice, and suppresses colorectal and hepatic metabolic and digestive processes through Cmah inhibition.